The relationship between social networking sites and adolescents social involvement: participation in offline activities and the role of social support - Sandra Rós Steinarsdóttir 1988- (2015)
Former studies have found that excessive internet use can lead to social isolation, however more recent studies have found that social networking sites can in fact be beneficial as they can enhance social development. The aim of the current study was to examine the relationship between social networking sites and adolescents´ participation in offline activities, and how perceived peer support can effect that relationship. It was hypothesized that adolescents that spend more time using social networking sites participate more in offline activities, and that perceived peer support has an additive effect on that relationship. The present study used data from the 2013 Youth in Iceland survey, conducted by the Icelandic Centre for Social Research and Analysis (ISCRA) and the sample included 2070 adolescents in the age range from 16 to 20 years. Results were examined using multiple regression. Findings indicated that with more time spent using social networking sites, participation in offline activities increased and peer support had an additive effect on offline activity. Keywords: social networking sites, offline activity, social support, adolescents, social development. Fyrri rannsóknir hafa leitt í ljós að aukin netnotkun geti leitt til félagslegrar einangrunar, þrátt fyrir það hafa nýlegri rannsóknir sýnt fram á að samfélagsmiðlar geti haft jákvæðar afleiðingar þar sem þeir geta aukið félagslegan þroska. Markmið þessarar rannsóknar var því að skoða sambandið á milli samfélgasmiðla og félagslegrar þátttöku unglinga utan veraldarvefsins og hvernig félagslegur stuðningur getur haft áhrif á það samband. Gert var ráð fyrir því að þeir unglingar sem eyða meiri tíma á samfélagsmiðlum, taki meiri þátt í félagslegum athöfnum utan veraldarvefsins og að félagslegur stuðningur auki þátttöku þeirra. Rannsóknin notaði fyrirliggjandi gögn frá rannsókninni Ungt fólk 2013, sem framkvæmd var af Rannsóknir og greining, og samanstóð úrtakið af 2070 unglingum á aldrinum 16-20 ára. Notuð var margvíð aðhvarfsgreining til þess að ...